HIV/AIDS SEBAGAI “RUANG” PELAYANAN PASTORAL GEREJA - Robinson Simanungkalit (Institut Agama Kristen Negeri Tarutung, 2019)
It is important to explain some important things on Human Immunodeficiency Virus (HIV) or Acquired Immunodeficiency Syndrome (AIDS). This study was aimed to to provide a proper understanding on the HIV/AIDS. Consequently, this study described what the HIV/AIDS is, the history of the emergence of HIV/AIDS, the transmission of HIV/AIDS, and the effects of HIV/AIDS on infected human. People infected with HIV and AIDS are referred to as PLWHA (People living with HIV and AIDS). They may be church citizens. Therefore, the church must not